2009
DOI: 10.1253/circj.cj-08-0866
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis and Characteristics of the Electrograms Recorded Within the Non-Coronary Aortic Sinus of Valsalva

Abstract: Circ J 2009; 73: 838 -845 ecent studies have demonstrated that some supraventricular tachycardias that have their origins near the atrioventricular node (AVN) or His-bundle region can be eliminated by radiofrequency (RF) catheter ablation from the non-coronary sinus of Valsalva (NSV). [1][2][3][4][5][6] We have also reported 2 cases of supraventricular tachycardias, which consisted of an atrial tachycardia (AT) 1 and atrioventricular (AV) orthodromic tachycardia (AVRT). 2 However, the characteristics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In most of these studies, this AT was diagnosed in accordance with the original report 10 . The main criteria, used in multiple previous observations, include a V‐A‐A‐V response upon ventricular induction or entrainment, 35–39,43,44,46–48,50,51 AV block during the ongoing tachycardia, 32,33,35,38–40,42–44,47,48,51 VA dissociation during ventricular overdrive stimulation of the tachycardia, 35,38,40,42,43,47,49–51 a variability of the atrial cycles preceding the ventricular cycles during tachycardia, 33,35,38,40,42,43,47,50,51 absence of VA linking during differential atrial entrainment stimulation 35,44,46,48,51 and a non‐reproducible atrial activation sequence with ventricular stimulation during tachycardia 32,33,35,37,38,43,50,51 . However, it has now been shown that these criteria can all be satisfied in patients presenting with sup‐F/S‐AVNRT 3–5,17,52 .…”
Section: Discussionmentioning
confidence: 99%
“…In most of these studies, this AT was diagnosed in accordance with the original report 10 . The main criteria, used in multiple previous observations, include a V‐A‐A‐V response upon ventricular induction or entrainment, 35–39,43,44,46–48,50,51 AV block during the ongoing tachycardia, 32,33,35,38–40,42–44,47,48,51 VA dissociation during ventricular overdrive stimulation of the tachycardia, 35,38,40,42,43,47,49–51 a variability of the atrial cycles preceding the ventricular cycles during tachycardia, 33,35,38,40,42,43,47,50,51 absence of VA linking during differential atrial entrainment stimulation 35,44,46,48,51 and a non‐reproducible atrial activation sequence with ventricular stimulation during tachycardia 32,33,35,37,38,43,50,51 . However, it has now been shown that these criteria can all be satisfied in patients presenting with sup‐F/S‐AVNRT 3–5,17,52 .…”
Section: Discussionmentioning
confidence: 99%
“…53 The aforementioned anatomic features of the 3 aortic sinuses are responsible for the differences in the electrogram recordings within these aortic sinuses: 37,43 the NSV electrograms during sinus rhythm have a larger atrial amplitude than ventricular amplitude, and the ratio of the atrial amplitude to the ventricular amplitude is usually >1, which is apparently different from the LSV and RSV electrograms (Figure 7). 37 Analysis of the electrogram is helpful for identifying the correct positioning of the mapping/ablation catheter at the aortic sinuses of Valsalva during the ablation procedure. Fortunately, most reported cases of catheter ablation of NSV tachycardias originating from near the AV node or Hisbundle region have not resulted in impairment of AV conduction.…”
Section: Specific Considerations For Catheter Ablation Within the Aormentioning
confidence: 99%
“…However, during tachycardia, it is difficult to confirm whether or not there is a Hisbundle potential, probably because of greater baseline drift and artifact during the tachycardia than during sinus rhythm or a wider distance between the His-bundle region and the ablation catheter during the tachycardia than during sinus rhythm (Figure 8). 37 Therefore, the presence of a His-bundle potential during sinus rhythm should be assessed before ablation at the NSV. To avoid impairment of AV conduction during RF energy delivery, it is useful to be aware of any prolongation of the PQ, A-H, or H-V interval.…”
Section: Specific Considerations For Catheter Ablation Within the Aormentioning
confidence: 99%
See 1 more Smart Citation
“…7-9,11, 12 The origins of focal VTs/PVCs were distributed at RVOT, the lateral RV, His bundle region, tricuspid annulus, aortic sinus cusp, and LV endocardium, and those of macroreentrant VTs were distributed at RVOT, lateral RV, and LV endocardium. [13][14][15] In focal VTs/PVCs, activation occurred from the VT/PVC focus, where VUE exhibited a QS or qRS pattern depending on the case, and from which activation spread out toward the entire ventricle. RFA targeting the VT/PVC focus resulted in elimination of almost all VTs/PVCs, even if VT/PVC focus was multiple and changed in location after each RF application.…”
Section: Main Findingsmentioning
confidence: 99%